Diskordansi Kadar CRP dan LED pada Pasien DM Tipe-2 dengan Ulkus Kaki Diabetik Analisis dengan Pendekatan Biofisika - Arshy Prodyanatasari; Mely Purnadianty; Mardiana Prasetyani Putri; Novia Agustina; Isni pra fitrilia (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2026)
Discordance between C-Reactive Protein (CRP) levels and Erythrocyte Sedimentation Rate (ESR) in type-2 diabetes mellitus patients with ulcers is frequently encountered in clinical practice, yet the underlying biophysical mechanisms remain largely unexplored. This study aimed to analyze the effect of CRP levels on erythrocyte membrane zeta potential and ESR in type-2 diabetes mellitus patients with ulcers. An observational analytic study with a cross-sectional design was conducted from June to July 2025 at Daha Husada Hospital, Kediri City. The population comprised all 85 inpatients with type-2 diabetes mellitus and ulcers in 2024, with a sample of 20 patients selected through purposive sampling based on inclusion and exclusion criteria. Primary data included CRP level examination (latex agglutination method), ESR (Westergren method), and erythrocyte membrane zeta potential (zeta potential analyzer). Data were analyzed using Pearson correlation and linear regression tests with SPSS version 25 (p<0.05). The results showed that among 20 respondents, 18 patients (90%) had negative CRP (<6 mg/L) and 2 patients (10%) had positive CRP. A total of 12 patients (60%) exhibited increased ESR, of which 10 (55.6%) had negative CRP. Both patients with positive CRP showed highly significant ESR increases (75 mm/hour and 110 mm/hour). This study confirms the presence of discordance between CRP and ESR in half of the respondents, indicating the role of erythrocyte membrane zeta potential as a biophysical mediator in determining ESR. Further research with direct zeta potential measurement and molecular form analysis of CRP is essential to strengthen these findings.